(untitled) (Progressive Agriculture, 2014)
Anoestrus is considered as one of the most prevalent reproductive disorders in dairy cows and may occur due to hormonal imbalance, nutritional deficiency and disease conditions. Proper diagnosis and treatment are essential to overcome this disorder to make dairy herd profitable. Therefore, the aim of study was to determine effects of hormonal and nutritional treatments on induction of oestrus and conception in postpartum anoestrus cows. Effects of BCS and parity of anoestrus cows were also considered during treatment. Seventy two cross-breed cows having ?60 days postpartum period were used, which were allotted for two treatment groups. Forty cows were treated with hormone (GnRH and PGF2? ) and rest 32 cows were with nutritional supplement. AI was performed in cows in observed oestrus and the conception was determined by transrectal ultrasonography between 28-35 days post-Al. 75% cows showed oestrus in hormonal treatment groups whereas 56.3% cows in nutritional treatment group. Moreover, the conception rate was significantly (P<0.05) higher in cows (57.5%) received hormonal treatment compared to that of cows (40.6%) in nutritional treatment counterpart. Highest conception rate was also observed (69.2%) in GnRH treated cows having BCS 2-2.5. Cows with parity 1-3 responded better to treatment and had higher conception rate. These results suggest that diagnosis of ovarian activities and reproductive disorders with the help of ultrasonography can lead to use appropriate techniques for treatment as well as to improve reproductive efficiencies of cows in case of postpartum anoestrus. DOI: http://dx.doi.org/10.3329/pa.v24i1-2.19109 Progress. Agric. 24(1&2): 93 - 100, 2013